2001
DOI: 10.1088/0954-3899/28/1/308
|View full text |Cite
|
Sign up to set email alerts
|

Multiskyrmions and baryonic bags

Abstract: Analytical treatment of skyrmions given by rational map (RM ) ansaetze proposed recently for the Skyrme model is extended for the model including the 6-th order term in chiral field derivatives in the lagrangian and used for the calculations of different properties of multiskyrmions. At large baryon numbers the approximate solutions obtained are similar to the domain wall, or to spherical bubbles with energy and baryon number density concentrated at their boundary. Rigorous upper bound is obtained for the mass… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
82
0

Year Published

2001
2001
2012
2012

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 59 publications
(87 citation statements)
references
References 25 publications
(152 reference statements)
5
82
0
Order By: Relevance
“…This ramp profile approximation replaces the profile functions by those which are piecewise linear, an idea first used in [15,16]. It was shown that this approximation is in good agreement with the rational map ansatz solutions, and by using it, solutions with a very high number of baryons existing as N thin shells of small thickness stacked together can be produced numerically.…”
Section: The Rational Map Ansatzmentioning
confidence: 99%
“…This ramp profile approximation replaces the profile functions by those which are piecewise linear, an idea first used in [15,16]. It was shown that this approximation is in good agreement with the rational map ansatz solutions, and by using it, solutions with a very high number of baryons existing as N thin shells of small thickness stacked together can be produced numerically.…”
Section: The Rational Map Ansatzmentioning
confidence: 99%
“…This is inspired by the work of Kopeliovich [13] [14] except that our ansatz has to be piecewise linear to be able to generate configurations with a huge number of layers. After defining the ansatz for an arbitrary number of layers, we will show that for a single layer configuration the ansatz produces configurations that are in good agreements with the rational map ansatz configuration.…”
Section: The Ramp-profile Approximationmentioning
confidence: 99%
“…There were number of theoretical predictions by using various models [3], the quark cluster model [10], the quark-delocation model [11,12], the chiral SU(3) quark model [13], the flavor SU(3) skyrmion model [14]. Lomon predicted a deuteron-like dibaryon resonance using R-matrix theory [15].…”
Section: Introductionmentioning
confidence: 99%